Adsorption of as(V), Cd(II) and Pb(II), in multicomponent aqueous systems using activated carbons - Pirila M. (2017)
The project CIMO North-South-South‘‘PROENV2’’, theAdMAtU–project (AKVA Program) financed by the Academy ofFinland, and HYMEPRO financed by the Finnish FundingAgency for Innovation (Tekes) are acknowledged for the financial support. The National University of Tumbes (ProyectoCanon – Resoluci ?on N80722-2014/UNT-R) and the PeruvianNational Council for Science and Technology (CONCYTEC)(Proyecto. No. 002/PE/2012) are gratefully recognized for theirsupport. The authors also want to thank their home universities for their support.